Extracellular vesicles in Niemann pick disease type C: current knowledge and future opportunities - Hawthorne, Sarah Catherine B.; Sandau, Ursula S.; Saugstad, Julie A. (Frontiers in Cellular Neuroscience, 2026)
Niemann Pick Disease Type C (NPC) is a rare neurodegenerative disease that primarily affects children. It is caused by mutations in the NPC1 or NPC2 genes, which encode proteins that transport cholesterol out of the endolysosomal organelles. Endolysosomal compartments also produce extracellular vesicles (EVs), which have emerged as key players in human disease. There is rapidly growing interest in how NPC cellular pathology impacts EV biology: of the 18 peer-reviewed publications on this topic, 13 were published within the last 5 years. Collectively, the existing literature suggests that the NPC proteins play key roles in EV biogenesis and uptake, that EV concentration and cargo are fundamentally altered in samples with NPC1/2 protein dysfunction, and that EVs may contribute to the therapeutic effects of NPC treatments. To better elucidate the connections between NPC and EVs further research is needed, especially in patient samples. Ultimately, a better understanding of the role of EVs in NPC will likely shed light on basic EV biology, related cellular neuropathologies, and a rare childhood disease that currently has no cure.